Upaya Guru Dalam Mengoptimalkan Pembelajaran Sosiologi di SMA Negeri 8 Kupang - Neri Yustina Auw (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
The objectives of this study were to discover (1) sociology teachers' efforts to improve sociology learning and (2) sociology teachers' obstacles in facing the students. Qualitative methods are used in this study. Besides, observation, interviews, and documentation were used to collect data. Data reduction, data presentation, and data analysis/data verification are the data analysis techniques. The study results show teachers' efforts have been made to optimize learning. Specifically, teachers are attempting to do lesson plans, implement them in the classroom, and motivate students. However, the teacher's limitations include the need for more learning media, lack of classroom management, and lack of evaluation.